TINJAUAN MASHLAHAH TERHADAP SANKSI PIDANA POLIGAMI DALAM DRAFT RKUHP PASAL 465-466 - Fahmil Huda Dinil Futra; Ismail Ismail; Edi Rosman (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2019)
Polygamy is a permissible and justified religion in Islam. The practice of polygamy was done long before the Islamic religion came until the hereditary is done until now. Polygamy practiced in Indonesia itself is governed by Law No. 1 of 1974 and government Regulation number 9 the year 1975. The laws and regulations of the Government shall be governed by the reason of polygamy, polygamy requirement to the procedure which must be taken by a person to polygamy. Not only that, seeing the phenomenon of polygamy practiced by the community, it appears the idea for the government to set the polygamy practice in order so that all people who polygamy meet the requirements and procedures that have been established. The idea was designed in the draft RKUHP article 465-466 which threatens with imprisonment and criminal penalties for illegal polygamy or those who do not meet these requirements and procedures. Therefore it is necessary to Further analysis related to the pipetting of polygamists who are illegal in Indonesia. The research uses library research. The data collection technique used is to take direction from the books that contain the idea of Maqashid Syariah theory, Indonesian marriage Law, and books related to polygamy. In the data processing using the analysis method of content (content analysis). While in drawing conclusions using the deductive method whereby the collected data is processed selectively and systematically then it is placed a special conclusion that is the result of the research. The results of this discussion showed that the design was to realize Mashlahah in order to save women's rights and maintenance to women's honors.